Hot Pin Pull Method - New Test Procedure for the Adhesion Measurement for 3D-MID - Goth, Christian; Kuhn, Thomas; Gion, Gerald; Franke, Jörg (11th International Congress Molded Interconnect Devices, 2014)
The adhesion test of metallic structures on MID (Molded Interconnect Devices) parts is an unsolved issue. So far no method really works reliably. The test methods which are conventionally used are the pull-off test and the shear-test. Both show large standard deviation and the reproducibility is not assured. Nordson DAGE has introduced the new micro-material testing system 4000Plus. This device enables a new test method for the determination of the adhesion strength of MID structures using the hot pin pull (hot bump pull) method. Copper pins (tinned or untinned) are heated up with a user defined temperature profile, soldered to a metallized structure on the MID and then removed vertically upward, while the force is recorded. In this contribution investigations with this new test method are presented.
Keywords: 3D-MID; E|P; Elektronikproduktion; Zuverlässigkeit